2022
DOI: 10.1210/endocr/bqac201
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone as a Possible Contributor to Eye Diseases

Abstract: Aldosterone, an effector molecule of the renin-angiotensin-aldosterone system (RAAS), has been receiving more attention in the field of ophthalmology because of its possible role in the pathogenesis of various eye diseases or abnormalities; potentially, it may even become a target for their treatment. Primary aldosteronism, a typical model of a systemic aldosterone excess, may cause vision loss due to various ocular diseases, such as retinal vein occlusion, central serous chorioretinopathy, and possibly, glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Meanwhile, VEGF mediates the breakdown of the BRB to cause diabetic macula edema (DME) and promotes pre-retinal neovascularization, which leads to vitreous hemorrhage, tractional retinal detachment, and neovascular glaucoma ( 104 ). Therefore, intravitreal injection of anti-VEGF agents has become the standard treatment to improve visual acuity in DME ( 105 ).…”
Section: The Effective and Potential Therapeutic Targets Of Raasmentioning
confidence: 99%
“…Meanwhile, VEGF mediates the breakdown of the BRB to cause diabetic macula edema (DME) and promotes pre-retinal neovascularization, which leads to vitreous hemorrhage, tractional retinal detachment, and neovascular glaucoma ( 104 ). Therefore, intravitreal injection of anti-VEGF agents has become the standard treatment to improve visual acuity in DME ( 105 ).…”
Section: The Effective and Potential Therapeutic Targets Of Raasmentioning
confidence: 99%
“…While some kidney-focused clinical studies suggest a deeper perspective, Higashide T et al. found that ROS accumulation can also promote the increase of aldosterone in patients with aldosteronism and eye diseases ( 39 ). However, Reina-Couto et al.…”
Section: Effects Of Aldosterone-mediated Oxidative Stress and Vascula...mentioning
confidence: 99%